A case of perforated immune-related colitis complicated by cytomegalovirus infection during treatment of immune-related adverse effect in lung cancer immunotherapy. (2023) - Nakai, Masahiro; Kai, Yoshiro; Suzuki, Kentaro; Matsuda, Masayuki; Kikukawa, Shoma; Masuda, Hiroyuki; Soga, Masahiro; Ueda, Takeshi; Yoshimura, Atsushi; Takano, Masato; Hontsu, Shigeto; Uno, Kenji; et al.
Abstract: Although immune checkpoint inhibitors (ICIs) can be used for lung cancer treatment, the activated immune response may cause immune-related adverse effects (irAEs). We present here a case of cytomegalovirus (CMV) enterocolitis during steroid therapy for an irAE. A 70-year-old man diagnosed with small-cell lung carcinoma (limited disease) received radiotherapy plus two chemotherapy cycles of cisplatin and etoposide. The tumor exhibited complete response but recurred after 3 years. After treatment with two cycles of carboplatin, etoposide, and atezolizumab, an inhibitors of programmed cell death receptor-1, he was switched to atezolizumab every 3 weeks for maintenance therapy. Diarrhea occurred after nine atezolizumab doses. With a strong suspicion of ICI-induced colitis, we administered methylprednisolone 500 mg for 3 days, followed by oral prednisolone 40 mg/day. Total colonoscopy during the treatment revealed mucosal inflammation of the total colon, suggesting immune-related colitis. Biopsies from the ulceration revealed crypt abscess with highly infiltrative plasma cells and lymphocytes. Furthermore, immunohistochemical staining showed positivity for CMV. With no improvement in watery diarrhea, the prednisolone dose was increased to 80 mg/day on the 11th day, and ganciclovir was additionally administered twice daily on the 26th day. On the 28th day, the patient had abdominal pain, and abdominal computed tomography revealed free air, resulting in the diagnosis of colon perforation. He underwent subtotal colectomy followed by ileostomy as emergency surgery. A colon specimen revealed colitis with CMV infection. We describe colon perforation in a patient with CMV enterocolitis complicated by refractory immune-related colitis.